Catholic interview : inter-departmental correspondence (copy) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
806-0028-001 DR. H.B. MORGAN. MISS F. McDONALD. Social Insurance. 12th November, 1936. CATHOLIC INTERVIEW. Yes, agreeable. So long as the report is regarded as a confidential one, and I am sure Mr. Middleton will treat it so. - He can certainly have it. 292C/806.1/1/28